Relationships between training load, sleep duration, and daily well-being and recovery measures in youth athletes - Sawczuk, T.; Jones, B.; Scantlebury, S.; Till, K. (Pediatric Exercise Science, 2018)
Purpose: To assess the relationships between training load, sleep duration, and 3 daily well-being, recovery, and fatigue measures in youth athletes. Methods: Fifty-two youth athletes completed 3 maximal countermovement jumps (CMJs), a daily well-being questionnaire (DWB), the perceived recovery status scale (PRS), and provided details on their previous day`s training loads (training) and self-reported sleep duration (sleep) on 4 weekdays over a 7-week period. Partial correlations, linear mixed models, and magnitude-based inferences were used to assess the relationships between the predictor variables (training and sleep) and the dependent variables (CMJ, DWB, and PRS). Results: There was no relationship between CMJ and training (r=-.09; ±.06) or sleep (r=.01; ±.06). The DWB was correlated with sleep (r=.28; ±.05, small), but not training (r=-.05; ±.06). The PRS was correlated with training (r=.23; ±.05, small), but not sleep (r=.12; ±.06). The DWB was sensitive to low sleep (d=-0.33; ±0.11) relative to moderate; PRS was sensitive to high (d=-0.36; ±0.11) and low (d=0.29; ±0.17) training relative to moderate. Conclusions: The PRS is a simple tool to monitor the training response, but DWB may provide a greater understanding of the athlete`s overall well-being. The CMJ was not associated with the training or sleep response in this population.